Bilateral ossified pterygospinous ligament and its clinical significance - Raju, S; Sujatha, M; Indira Devi, B; Sirisha, B; Sri Devi, P (Department of Surgery, UKM Medical Centre, 2012)
The ossification of the pterygospinous ligament form the bridge known as pterygospinous bony bridge and it may create a pterygospinous foramen. Close location of this ossified pterygospinous ligament to the foramina ovale, can entrap the mandibular nerve and its branches which emerges through the foramen ovale and may produce the clinical condition known as mandibular neuralgia. Presence of such ossified pterygospinous ligament may also interfere with the mandibular nerve block. Here, we report a rare case of ossified pterygospinous ligament bilaterally in a dried adult skull. The measurements of variant pterygospinous foramen were recorded as 4.25 mm horizontally and 4.55 mm vertically, on the right side and 4mm, 4.10 mm on the left side. This variation is clinically important for Surgeons, Neurologists and Anesthetists.